PRESTASI POMPA SENTRIFUGAL TIPE OVERHUNG UNTUK APLIKASI INDUSTRI DENGAN METODE REVERSE ENGINEERING DAN CFD - Yamin, Mohamad; Irawan, Rudi; Mahandari, Cokorda Prapti; Ariandi, Rian Dwi; Firmansyah, Riyan; Alfasha, Muhammad Zidan; Suharto, Suharto (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
Indonesia faces various challenges in achieving net zero emissions, energy crises, and urgent agricultural irrigation needs. In this context, centrifugal pumps play a crucial role in various industrial applications and irrigation systems. However, performance curve data for pumps is often unavailable, particularly for older pumps or those with lost documentation. This study aims to develop new performance curves for centrifugal pumps using Reverse Engineering (RE) based on 3D scanning and Computational Fluid Dynamics (CFD) simulation. The process begins with geometric modeling of the pump using 3D scanning to obtain accurate data regarding the pump’s physical shape. The model is then used in CFD simulations with the k-epsilon (k-ε) turbulence model and SIMPLE method to analyze flow characteristics and pump performance. Simulation results show that the deviation in efficiency and power compared to existing experimental data is below 2%, with a mesh size of 0.00005 mm providing optimal results in terms of accuracy and computational efficiency. This research demonstrates that developing performance curves using RE and CFD methods can address issues of missing data and provide a solid foundation for design improvements and efficient operation of centrifugal pumps. The findings have the potential to enhance operational efficiency of pump systems and support environmental impact mitigation efforts through pump technology optimization.